Optimization of Dielectric Strength of Polymeric Composite Insulation Using Response Surface Methodology - Aman, Aminudin (2012)
This paper presents the development of a newly polymeric composite for high voltage outdoor insulation. The composites were prepared by melt compounding with a Haake internal mixer, then subjected to the dielectric strength test complying with BS EN 60243-1:1998. The purpose of this research is to determine the optimum ratio of the filler that maximize the dielectric strength of this composite. For this optimization, the Design of Experiment with Response Surface Methodology (RSM) statistical technique was applied. From thescreening factor, commercial wollastonite and alumina trihydrate were identified as a significant factor for dielectric strength output response. From analysis of variant (ANOVA), the model is adequate with P value greater than 0.0500 and the accuracy is 91.04%. The optimum value for the predicted dielectric strength is 36.72kV for the composite compound of 20-80 commercial wollastonite-polypropylene wt% with 100pph alumina trihydrate. Deviation with the actual value is around 9.18%.